PENGARUH SUPERVISI AKADEMIK, MOTIVASI KERJA TERHADAP KINERJA GURU SMP DAN MTs DI KECAMATAN SUBAH DAN PECALUNGAN KABUPATEN BATANG - Nufindah Pribadi (Magister Manajemen Pendidikan, Universitas PGRI Semarang, 2023)
The formulation of the problem in this research is 1) is there any effect of academic supervision on the performance of SMP and MTs teachers in Subah and Pecalungan Districts, Batang Regency, 2) is there an effect of work motivation on the performance of SMP and MTs teachers in Subah and Pecalungan Districts, Batang Regency, 3) is there any effect of academic supervision and work motivation on the performance of teachers in SMP and MTs in Subah and Pecalungan Districts, Batang Regency.This study uses a quantitative correlation approach. Data mining using a questionnaire instrument. The research locations were public junior high schools and MTs in Subah and Pecalungan sub-districts. Test Instrument is a test of validity and reliability. Prerequisite test using normality test, linearity test, multicollinearity test, homogeneity test. Data analysis used correlation test, simple linear regression test and multiple linear regression test.The results of the study (1) the effect of academic supervision on the performance of SMP and MTs teachers in Subah and Pecalungan Districts, Batang Regency. Based on the Fcount value of 134.127 > Ftable 3.93 with a significance value of 0.000 <0.05. which means H0 is rejected and Ha is accepted. The hypothesis which reads